Noise free fully homomorphic encryption scheme over non-associative algebra - Mustafa, Iqra; Mustafa, Hasnain; Azar, Ahmad Taher; Aslam, Sheraz; Mohsin, Syed Muhammad; Qureshi, Muhammad Bilal; Ashraf, Nouman (My University, 2020)
Among several approaches to privacy-preserving cryptographic schemes, we have concentrated on noise-free homomorphic encryption. It is a symmetric key encryption that supports homomorphic operations on encrypted data. We present a fully homomorphic encryption (FHE) scheme based on sedenion algebra over finite Zn rings. The innovation of the scheme is the compression of a 16-dimensional vector for the application of Frobenius automorphism. For sedenion, we have p16 different possibilities that create a significant bijective mapping over the chosen 16-dimensional vector that adds permutation to our scheme. The security of this scheme is based on the assumption of the hardness of solving a multivariate quadratic equation system over finite Zn rings. The scheme results in 256n multivariate polynomial equations with 256+16n unknown variables for n messages. For this reason, the proposed scheme serves as a security basis for potentially post-quantum cryptosystems. Moreover, after sedenion, no newly constructed algebra loses its properties. This scheme would therefore apply as a whole to the following algebras, such as 32-dimensional trigintadunion.
Keywords: Automorphism Aut(V); Frobenius automorphism φ; Fully homomorphic encryption; Multivariate polynomial equations; Sedenion; Totally isotropic subspaces